ANALISIS KESALAHAN MAHASISWA TADRIS MATEMATIKA DALAM MENYELESAIKAN SOAL PERSAMAAN DIFERENSIAL BERDASARKAN KRITERIA WATSON - Heni Lilia Dewi; Fatimah Zikra Amalia (Al-Fikru : Jurnal Pendidikan Dan Sains, 2023)
Mathematics is an important field of study that is taught at various levels, one of them is college. To become a Bachelor of Mathematics Education, one of students' mathematics skills can be seen in the ability to solve problems. This study aimed to find out the error of Mathematics Education students in solving Differential Equation problems based on Watson's criteria, and find out the factors causing the error to occur. This research is important to do to find out the errors in solving Differential Equation problems and the factors causing the error to occur. The research design and approach of this research was Descriptive Qualitative. Data was obtained through written test instruments, interviews and documentation. The analysis technique used to analyze student error was based on Watson's 8 criteria, while the research data analysis were data reduction, data presentation and drawing conclusion. The results found that the percentageof inappropiate data (28.11%), inappropiate procedure (24.32%), omitted data (27.57%%), omitted conclusion (84.86%), response level conflict(2.16%%), undirected manipulation (4.86%), skill hierarchy problems (6.49%), and above others (64.32%). The percentage of error that occurred in 37 students from all questions based on Watson's 8 criteria was 30.34%. Factors that cause errors are: (1) internal factors,students do not fully remember the material being tested, they have not mastered the material tested properly and are not thorough when doing the test; (2) external factors, students do not focus when doing the test, work together with friends, and incomplete notes.Keywords: Error Analysis, Cause Factors, Watson Categories, Differential Equations.